Estudo toponímico bilíngue Português-Libras dos espaços de serviços públicos essenciais de Feira de Santana - Ba - Macambira, Thaiane Souza (2025)
The naming of urban spaces, more than a linguistic practice, constitutes an act of cultural construction and affirmation of belonging. By investigating the motivations that guide this process, Toponymy makes it possible to understand how different linguistic communities perceive and re-signify the territory in which they live. From this perspective, this dissertation, linked to the Graduate Program in Linguistic Studies at the State University of Feira de Santana (UEFS), is dedicated to a bilingual toponymic study (Portuguese and Brazilian Sign Language – Libras) of essential public services in Feira de Santana, Bahia, aiming to inventory and analyze the motivations underlying the names assigned to these spaces. The corpus comprises 85 toponyms in each language, systematized in lexicographic-toponymic records and classified according to categories inspired by the Strike Law (Law No. 7.783/1989). The theoretical framework is grounded in studies of Lexicology and Toponymy (Biderman, 1984; 1998; 2001; Dauzat, 1926; Dick, 1990; 1992; Seabra, 2004; 2006; Vilela, 1983; Barreiros, 2017) as well as research on Libras (Felipe, 2006; Ferreira, 1995; Souza Júnior, 2012; Quadros & Karnopp, 2019; Quadros, 2020; Sousa, 2022). The results showed, in Portuguese, the predominance of acronym toponyms (23%) and socio-toponyms (20%), while in Libras mimetotoponyms were predominant (51%), followed by grapho-toponyms and socio-toponyms. These differences reveal that, while naming in Portuguese privileges abbreviations and a market-oriented logic, the Deaf community grounds its choices in visual and iconic elements. As a product, the YouTube channel and Instagram page Feira Acessível – Serviços Essenciais were created, gathering and organizing the collected signs. This research contributes to bilingual toponymic studies, expands the lexical repertoire in Libras, and highlights the urgent need for accessibility policies that ensure the Deaf community’s full exercise of their rights in the city’s essential service spaces.